2021
DOI: 10.2174/0929867328666210526100147
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: The Significance of Platelets, Mitochondria, Vitamin D, Serotonin and the Gut Microbiota

Abstract: : We provide a brief review of the significance of platelets, mitochondria, vitamin D, serotonin and the gutmicrobiome in COVID-19. We hypothesize that hyperactive platelets and mitochondrial dysfunction, as well as low vitamin D level, gut dysbiosis and increased serum serotonin produced by enterochromaffin cells, may all represent important aspects in the pathophysiology of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 203 publications
(328 reference statements)
0
2
0
Order By: Relevance
“…Such neuropathological alterations may also provide an explanation as, why acute neurocognitive complaints posed a “red flag” of subsequent mental health deterioration in our study cohorts. Other factors, such as Vitamin D, mitochondrial dysfunction, or gut dysbiosis, might also link COVID-19 pathobiology and mental health ( 40 ). In Random Forest modeling of mental health scoring in our study collectives, impaired physical performance following COVID-19 was found to impact particularly depression, OMH, and QoL rating.…”
Section: Discussionmentioning
confidence: 99%
“…Such neuropathological alterations may also provide an explanation as, why acute neurocognitive complaints posed a “red flag” of subsequent mental health deterioration in our study cohorts. Other factors, such as Vitamin D, mitochondrial dysfunction, or gut dysbiosis, might also link COVID-19 pathobiology and mental health ( 40 ). In Random Forest modeling of mental health scoring in our study collectives, impaired physical performance following COVID-19 was found to impact particularly depression, OMH, and QoL rating.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory and clinical research suggested that the well-known mitochondrial disorder responsible for different pathological states may come from an imbalance of the microbial regulation [185][186][187]. Microbiota-mitochondria disorders have been described in gastrointestinal diseases, such as in newonset Crohn's disease [188], in chronic intestinal inflammation and cancer [69], in neuropsychiatric diseases like autism [189], Parkinson's disease [190], Alzheimer's disease [179], post-traumatic stress disorder [191], depression [192], chronic fatigue syndrome [193], in metabolic diseases such as obesity and type 2 diabetes [194], in chronic Marijuana users [195], in exercise [196], in aging [197], and recently in COVID-19 [198]. Here below we discuss influences and potential benefits of some microbial metabolites and compounds on AMD.…”
Section: Microbial Metabolitesmentioning
confidence: 99%